2013
DOI: 10.1002/gcc.22067
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional nuclear telomere architecture changes during endometrial carcinoma development

Abstract: Endometrioid or type-I endometrial carcinoma (EC) develops from hyperproliferative glandular pathologies. Inactivation of the tumor suppressor gene PTEN is frequently associated with type-I EC. Using a previously characterized Pten heterozygous (Pten+/−) mouse model, this study investigates the three-dimensional (3D) telomere profiles during progression from hyperplastic lesions to EC to test the hypothesis that altered 3D telomere profiles can be detected prior to Pten loss in early hyperproliferative lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Having shown that HMGA2 diminishes telomere-mediated genomic instability in human cancer cells, we wanted to determine if the loss of this telomere protective role of HMGA2 involves changes in 3D telomere architecture [ 47 49 ]. For these studies, we used C1 cells +/− dox to regulate the level of endogenously produced HMGA2.…”
Section: Resultsmentioning
confidence: 99%
“…Having shown that HMGA2 diminishes telomere-mediated genomic instability in human cancer cells, we wanted to determine if the loss of this telomere protective role of HMGA2 involves changes in 3D telomere architecture [ 47 49 ]. For these studies, we used C1 cells +/− dox to regulate the level of endogenously produced HMGA2.…”
Section: Resultsmentioning
confidence: 99%
“…A significantly increased number of telomere aggregates was observed in atypical hyperplastic cells in a mouse models which is also a specific feature of cancer cells. Moreover, the PTEN heterozygous mouse model further demonstrated that 3D telomere architectural changes occur before the complete loss of PTEN and prior to the development of histological characteristics of atypical hyperplasia and endometrial carcinoma (251). Therefore, the presence of telomere aggregates in hyperproliferative lesions with atypical nuclei may render them to be precancerous changes.…”
Section: Endometriummentioning
confidence: 99%
“…In turn, the carcinoma in situ of the endometrium; also called intraepithelial neoplasia, progresses in some cases in less than a year to endometrial adenocarcinoma 114 . Among the molecular events associated with the progression of carcinomas in situ is the gain in the expression and activity of telomerase, as well as the extension of telomeres [115][116][117] . The 80% of sporadic endometrial adenocarcinomas show endometrioid histology 114 .…”
Section: Box 2 Conserved Process In Epithelial Carcinogenesismentioning
confidence: 99%